Сontralateral acute epidural hematoma after acute subdural hematoma removal using decompressive craniectomy: six cases and literature review - Sirko, Andriy; Poronik, Stanislav; Al-Ameer, Muaz Rugdi (Ukrainian Neurosurgical Journal, 2016)
Сontralateral acute epidural hematoma (AEDH) after acute subdural hematoma (ASDH) removal is an uncommon, but disastrous postoperative complication. Here we describe six own observations and provide analysis of 42 other cases relating to the above. Сontralateral AEDH after ASDH removal using decompressive craniectomy (DC) is diagnosed in 2.4-4.2% of cases. Main risk factors of contralateral AEDH development include: presence of fracture on the opposite side from the subdural hematoma; hematoma removal using DC; heavy injury (GCS 4-8); mechanism of injury – car accident or fall from a height; patient’s juvenile age. Сontralateral AEDH occurrence shall be excluded as soon as possible by performing verification brain CT in following cases: occurrence of intraoperative cerebral edema, rapid ICP growth, postoperative neurological disorder. Main reason of contralateral AEDH occurrence is the presence of arteria or vein damages in the fracture site. Urgent re-operation is indicated in all cases.